Nature's path : a history of naturopathic healing in America - Cayleff, Susan E., 1954- (Johns Hopkins University Press, 2016)
"In Nature's Path- the first comprehensive book to examine the complex history and culture of American naturopathy- Susan E. Cayleff tells the fascinating story of the movement's nineteenth-century roots."--Jacket